Application of Demonstration Methods Assisted Block Diagram Media to Increase Student Achievment in Geography Learning - Mita Rafinda Sari; Djoko Subandriyo; Sarwono Sarwono (PAEDAGOGIA, 2020)
The aims of this study were (1) to know the process of learning by using demonstration methods assisted block diagram media of students in class X social program 7 SMA Negeri 8 Surakarta. (2) to know the increase of geography learning result on the subject of Atmospheric Dynamics, students in class X social program 7 SMA Negeri 8 Surakarta Academic Year 2016/2017. The Research Approach was Classroom Action Research ( ACR), conducted in two cycles, each cycle consisted of planning, execution, observation, and reflection. The subject of the research is the class X Socia Program 7 even semester of SMA Negeri 8 Surakarta academic year 2016/2017, namely 27 students. The result of this study was (1) the implementation of the demonstration method assisted by block diagram media proved to maximize the learning process in students. (2)Application of demonstration methods assisted by block diagram media proved to increase the learning result of students, which is indicated by the student learning result.